PERAN KEMAMPUAN KOMUNIKASI TERHADAP SIKAP PERCAYA DIRI SISWA SEKOLAH DASAR - Lulu Luckyta; Astri Sutisnawati; Din Azwar Uswatun (PGSD Universitas Muria Kudus, 2020)
This research aims to describe the role of communication skills on the confident attitude of students in Negeri 1 Selabintana Elementary School. The method used in this study is qualitative-descriptive referring to the Miles design pattern and Huberman. The results of research analysis are obtained through field observation data retrieval techniques, and structured interviews, interviews are conducted with both informant namely high class teachers in state Elementary School 1 Selabintana. The results show that the students ' communication skills in the learning process are said to be good, whether referred to here is the students are able to convey the meaning of the message that they want to convey to the communicable by behave as it should be: directed, structured, clear in speaking or articulating articulation, regulating the use of language, language tone, appreciative of disagreements This communication skill has an impact on increasing student confidence in the final outcome of learning with maximum.